Preparation method and application of Bi-doped ZnIn2S4 / BiOBr heterojunction photocatalyst

The Bi-doped ZnIn2S4/BiOBr Z-type heterojunction structure was constructed by the one-step perovskite conversion method, which solved the problems of narrow spectral response and weak redox capabilities of traditional photocatalysts, and achieved efficient photocatalytic performance and low-cost production.

CN119819333AActive Publication Date: 2025-04-15HEBEI UNIV OF TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510031521.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

Traditional BiOBr and ZnIn2S4 photocatalysts have problems such as narrow spectral response, high photogenerated carrier recombination rate and low quantum efficiency, which limits their application and performance improvement.

Method used

The Bi-doped ZnIn2S4/BiOBr Z-type heterojunction structure was constructed using the one-step perovskite transformation method, which expanded the spectral response range and enhanced the redox capacity.

Benefits of technology

The photoabsorbing capacity, charge transfer efficiency and photogenerated carrier efficiency of the photocatalyst are significantly improved, the wastewater treatment efficiency is improved, and production costs and energy consumption are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819333A_ABST
    Figure CN119819333A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a Bi-doped ZnIn2S4 / BiOBr heterojunction photocatalyst and an application of the Bi-doped ZnIn2S4 / BiOBr heterojunction photocatalyst. The method adopts a perovskite one-step conversion method and comprises the following steps: firstly, adding indium chloride, zinc chloride and TAA into absolute ethyl alcohol to react to obtain ZnIn2S4; then adding the obtained ZnIn2S4, CsBr and BiBr3 into DMSO (Dimethylsulfoxide) to prepare a precursor solution, and then injecting the precursor solution into isopropanol to prepare Cs3Bi2Br9 / ZnIn2S4; and finally, dispersing the mixture into deionized water to obtain the Bi-doped ZnIn2S4 / BiOBr photocatalyst. The method has a remarkable effect in the aspect of organic dye sewage treatment, and the sewage treatment efficiency is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic materials, and specifically relates to a preparation method and application of Bi-doped ZnIn2S4 / BiOBrZ type heterojunction photocatalyst Background Art

[0002] The development of clean and sustainable energy technology has become an urgent need. Due to the successful synthesis of a variety of semiconductor photocatalysts, which can generate electron-hole pairs to trigger redox reactions, photocatalytic technology has great potential in many fields and can remove harmful gases and organic pollutants. Therefore, it has become a new means of governance and has received more and more attention. The development of nano and material science has made the design and modification of photocatalysts the key to improving efficiency. Traditional photocatalysts such as titanium dioxide, zinc oxide, and cadmium sulfide have advantages such as chemical stability and low cost, but have disadvantages such as narrow spectral response (low utilization rate of multi-response ultraviolet light energy), high recombination rate of photogenerated carriers, and low quantum efficiency, which limit their application and performance improvement. BiOBr has the advantages of wide visible light response, high conductivity, and excellent quantum efficiency compared with traditional photocatalysts, but is restricted by the problems of photogenerated carrier recombination, agglomeration, and light energy utilization; ZnIn2S4 has the advantages of simple preparation, low cost, and visible light response band gap, but its performance is limited by photogenerated carrier recombination, low solar energy conversion efficiency, and weak oxidation ability. Both need to be improved to improve photocatalytic performance.

[0003] BiOBr and ZnIn2S4 can improve the photocatalytic rate by constructing heterojunctions. Due to the different energy band structures of the two, the built-in electric field at the heterojunction interface under illumination causes the photogenerated carriers to migrate in a directional manner, reducing recombination; the light absorption range is also expanded, which can capture more light energy, thereby significantly improving the rate in photocatalytic applications, and performing better in treating pollutants and decomposing water to produce hydrogen. For example, HHSS-NH2@BiOBr / ZnIn2S4 (CN118594576A) and type II heterostructure BiOBr / ZnIn2S4 (CN118807794A) improve the photocatalytic rate by constructing heterojunctions. However, the preparation process of HHSS-NH2@BiOBr / ZnIn2S4 is complicated, and the multi-step reaction and strict condition control make it difficult to stabilize the quality and performance during industrial production, and the cost is high; the stability is limited, and factors such as temperature, humidity, and pH in the actual environment can easily cause its structural performance to change. Although the preparation process of type II heterostructure BiOBr / ZnIn2S4 is simple and the stability is good, the redox ability of photogenerated carriers is weak, which affects the reaction efficiency and leads to low efficiency; the light absorption range is narrow, concentrated in a certain band of visible light, and the absorption of other light is weak.

[0004] Therefore, it is urgent to propose a preparation method for BiOBr / ZnIn2S4, which can not only effectively expand the spectral response range of the material and enhance its redox ability, but also has simple and efficient synthesis process characteristics to meet the needs of practical applications and overcome the limitations of existing related materials and preparation methods. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method and application of Bi-doped ZnIn2S4 / BiOBr heterojunction photocatalyst in view of the shortcomings of the traditional photocatalyst preparation method, which has complicated steps and limited catalytic efficiency. In terms of material composition, the method innovatively introduces Bi doping and constructs a ZnIn2S4 / BiOBr Z-type heterojunction structure; in the preparation method, different from the traditional multi-step complex process, the perovskite one-step conversion method is adopted to achieve efficient and stable photocatalyst preparation. The present invention has a significant effect in treating organic dye wastewater and greatly improves the efficiency of wastewater treatment.

[0006] The technical solution of the present invention is:

[0007] A method for preparing a Bi-doped ZnIn2S4 / BiOBr heterojunction photocatalyst, the method comprising the following steps:

[0008] ZnIn2S4 was added to a Cs3Bi2Br9 precursor, and Cs3Bi2Br9 / ZnIn2S4 was prepared by an anti-solvent method. Cs3Bi2Br9 / ZnIn2S4 was dispersed in deionized water to obtain a Bi-doped ZnIn2S4 / BiOBr photocatalyst.

[0009] The molar ratio of Bi-doped ZnIn2S4 / BiOBr is BiOBr:ZnIn2S4=1:(0.015-0.075);

[0010] Specifically:

[0011] 1) Add indium chloride, zinc chloride and TAA to anhydrous ethanol, stir evenly and transfer to a polytetrafluoroethylene reactor, seal and react at 150-170 degrees for 10-14 hours, cool and wash with water, and dry to obtain ZnIn2S4;

[0012] Wherein, the molar ratio of indium chloride, zinc chloride and thioacetamide is 2:1:4;

[0013] 2) Adding ZnIn2S4, CsBr and BiBr3 obtained in step 1) into DMSO to prepare a precursor solution, stirring for 0.5 to 1.0 h, injecting the precursor solution into isopropanol, stirring for 1 to 3 min, and then centrifuging at 8000 to 10000 rpm / min for 1 to 3 min to separate a yellow precipitate, then washing the precipitate with ethanol, centrifuging, and drying at 50 to 70° C. to obtain Cs3Bi2Br9 / ZnIn2S4;

[0014] Wherein, the molar ratio of ZnIn2S4 to cesium bromide and bismuth bromide is (0.015-0.75):1.5:1;

[0015] Add 0.0010-0.010 mmol ZnIn2S4 per 10 ml DMSO; the volume ratio is precursor solution: isopropanol = 1:5-10;

[0016] 3) Dispersing the Cs3Bi2Br9 / ZnIn2S4 obtained in step 2) into deionized water, stirring, centrifuging, and vacuum drying to obtain a Bi-doped ZnIn2S4 / BiOBr photocatalyst.

[0017] Add 0.06-0.1g of Cs3Bi2Br9 / ZnIn2S4 per 10mL of deionized water;

[0018] The stirring time in step 3) is 5 to 15 minutes.

[0019] The Bi-doped ZnIn2S4 / BiOBr heterojunction photocatalyst prepared by the method is used to degrade Rhodamine B pollutants under visible light irradiation.

[0020] The Bi-doped ZnIn2S4 / BiOBr photocatalyst was uniformly dispersed in a rhodamine B aqueous solution and irradiated under visible light for 5 to 15 minutes.

[0021] The concentration of the Rhodamine B aqueous solution is 20 mg / L; 20 mg of Bi-doped ZnIn2S4 / BiOBr photocatalyst is added to every 20 mL of the Rhodamine B aqueous solution.

[0022] The essential features of the present invention are:

[0023] The present invention successfully synthesized Bi-doped ZnIn2S4 / BiOBr heterojunction photocatalyst by using a one-step perovskite conversion method, and realized Bi ion doping while forming a Z-type heterojunction, extending the light response range to the infrared region. Compared with independent BiOBr and ZnIn2S4 photocatalysts, the Bi-doped ZnIn2S4 / BiOBr composite material has superior light absorption capacity, enhanced charge transfer efficiency, and improved photogenerated carrier efficiency.

[0024] The beneficial effects of the present invention are:

[0025] (1) The present invention adopts a one-step strategy to synthesize Bi-doped ZnIn2S4 / BiOBr composite materials by converting ZnIn2S4 / Cs3Bi2Br9, and simultaneously realizes the construction of Z-type heterojunction and the doping of Bi ions, which is significantly different from the traditional multi-step complex and separate preparation method, greatly simplifies the process steps and improves production efficiency.

[0026] (2) The Bi-doped ZnIn2S4 / BiOBr photocatalyst prepared by the present invention is low-cost, the synthesis method is simple and efficient, and the entire experimental process does not require high-temperature synthesis, which not only reduces energy consumption costs, but also reduces equipment requirements.

[0027] (3) The Bi-doped ZnIn2S4 / BiOBr prepared by the present invention has a significant effect in the photocatalytic treatment of organic dye wastewater, and the degradation of organic dye wastewater is completed within 5 minutes, which greatly improves the efficiency of wastewater treatment.

[0028] (4) The photocatalyst synthesized by the present invention has good cycle stability. After five photocatalytic cycle degradations, the photocatalytic degradation effect does not decrease significantly and can be recycled and reused multiple times. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is the XRD pattern of the synthesized photocatalyst, where Figure 1 (a) is the XRD pattern of ZnIn2S4 synthesized in Example 1, Figure 1 (b) is the XRD pattern of the Bi-doped ZnIn2S4 / BiOBr photocatalyst synthesized in Example 1-4.

[0030] Figure 2 This is a SEM image of the photocatalyst synthesized in Example 1, wherein: Figure 2 (a) is a SEM image of the ZnIn2S4 photocatalyst synthesized in Example 1, Figure 2 (b) is the SEM image of Bi-doped ZnIn2S4 / BiOBr synthesized in Example 1.

[0031] Figure 3 This is a time-degradation rate diagram of the photocatalysts ZnIn2S4 and Bi-doped ZnIn2S4 / BiOBr synthesized in Examples 1-4 for decomposing Rhodamine B solution. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with specific implementation examples.

[0033] Embodiment 1:

[0034] (1) Dissolve 1 mmol of indium chloride tetrahydrate (InCl34H2O), 0.5 mmol of zinc chloride (ZnCl2) and 2 mmol of thioacetamide (TAA) in 30 mL of anhydrous ethanol and stir thoroughly for 60 min. Then, transfer the solution to a 50 mL polyvinyl fluoride reactor and react at 160°C for 12 h. After natural cooling, centrifuge with anhydrous ethanol and ultrapure water three times. The resulting product is dried at 70°C and ground into a uniform powder to obtain ZnIn2S4.

[0035] (2) 0.0045 mmol ZnIn2S4, 0.45 mmol cesium bromide (CsBr) and 0.3 mmol bismuth bromide (BiBr3) were added to 10 ml dimethyl sulfoxide (DMSO), stirred for 60 min, and then injected into 50 ml isopropanol while stirring. After stirring for 1 min, the yellow precipitate was collected by centrifugation at 10000 r / min for 3 min. The precipitate was washed three times with ethanol and then dried at 50°C to obtain Cs3Bi2Br9 / ZnIn2S4.

[0036] (3) 0.08 g of Cs3Bi2Br9 / ZnIn2S4 was dispersed in 10 ml of water, stirred for 10 minutes, and centrifuged at 10000 r / min for 3 minutes. The precipitate obtained by centrifugation was vacuum dried for 24 hours. The resulting product was Bi-doped ZnIn2S4 / BiOBr photocatalyst, in which the mass ratio of BiOBr to ZnIn2S4 was 1:0.015 (theoretical value), marked as BOB / ZIS-1.

[0037] During the synthesis of Cs3Bi2Br9, ZnIn2S4 will become Bi-doped ZnIn2S4 when it encounters BiBr3, while Cs3Bi2Br9 will decompose into BiOBr when it encounters water.

[0038] Figure 1 The prepared ZnIn2S4 in (a) and the standard PDF card (65-2023) are in good agreement, proving that ZnIn2S4 was successfully prepared. Figure 1 In (b), the XRD spectrum is mainly the peak of BiOBr. With the increase of ZnIn2S4 component, the XRD peak of ZnIn2S4 gradually appears, proving that the ZnIn2S4 / BiOBr composite material was successfully prepared.

[0039] Figure 2 (a) is the SEM of pure ZnIn2S4, where the flower-like morphology can be seen. Figure 2 (b) Some nanosheets with a size of 0.507 μm are loaded on the flower-like morphology, proving that BiOBr nanosheets are successfully loaded on ZnIn2S4.

[0040] Embodiment 2:

[0041] Compared with Example 1, the molar mass of ZnIn2S4 in step 2 is changed to 0 mmol, and the rest is the same as Example 1. The molar mass ratio of BiOBr to ZnIn2S4 in the synthesized Bi-doped ZnIn2S4 / BiOBr photocatalyst is 1:0, marked as BOB / ZIS-0.

[0042] Embodiment 3:

[0043] Compared with Example 1, the molar mass of ZnIn2S4 in step 2 is changed to 0.009 mmol, and the rest is the same as Example 1. The molar mass ratio of BiOBr to ZnIn2S4 in the synthesized Bi-doped ZnIn2S4 / BiOBr photocatalyst is 1:0.03, marked as BOB / ZIS-2.

[0044] Embodiment 4:

[0045] Compared with Example 1, the molar mass of ZnIn2S4 in step 2 is changed to 0.0018 mmol, and the rest is the same as Example 1. The molar mass ratio of BiOBr to ZnIn2S4 in the synthesized Bi-doped ZnIn2S4 / BiOBr photocatalyst is 1:0.075, marked as BOB / ZIS-3.

[0046] A set of experiments were conducted on the Bi-doped ZnIn2S4 / BiOBr photocatalyst obtained in Example 1, Example 2, Example 3 and Example 4 to catalyze and degrade organic dyes under visible light: Rhodamine B aqueous solution was used as a model sewage to evaluate the high photocatalytic activity of the catalyst. The experimental conditions were set as follows: a) 20 mg of Bi-doped ZnIn2S4 / BiOBr photocatalyst was dispersed in 20 mL of 20 mg / L Rhodamine B aqueous solution, and stirred for 30 minutes under dark conditions to allow Rhodamine B to reach adsorption-desorption equilibrium on the catalyst surface; b) A xenon lamp was used as the light source, and 0.5 ml of solution was taken out from the reactor every 2.5 minutes after the light was turned on. During illumination, the xenon lamp used a 420 nm filter to filter out light with a wavelength less than this, and the power of the xenon lamp was 300 W. Samples were taken every 2.5 minutes, centrifuged, and the changes in the ultraviolet-visible absorption peak of Rhodamine B in the solution were detected until the characteristic absorption peak of Rhodamine B could not be detected. The concentration value of Rhodamine B in the solution that reached adsorption equilibrium was defined as C0.

[0047] Depend on Figure 3 It can be seen that the Bi-doped ZnIn2S4 / BiOBr photocatalyst has excellent photocatalytic activity, especially the degradation rate of BOB / ZIS-1 after 5 minutes of illumination reaches 96%. It further shows that the Bi-doped ZnIn2S4 / BiOBr photocatalyst synthesized by the present invention is a good photocatalyst and has good application in the field of photocatalysis.

[0048] Matters not covered by the present invention are known technologies.

Claims

1. A method for preparing a Bi-doped ZnIn2S4 / BiOBr heterojunction photocatalyst, characterized in that: The method comprises the following steps: 1) Add indium chloride, zinc chloride and TAA to anhydrous ethanol, transfer to a polytetrafluoroethylene reactor after stirring, seal and react at 150-170°C for 10-14h, cool and wash with water, and dry to obtain ZnIn2S4; Wherein, the molar ratio of indium chloride, zinc chloride and thioacetamide is 2:1:4; 2) Adding ZnIn2S4, CsBr and BiBr3 obtained in step 1) into DMSO to prepare a precursor solution, stirring for 0.5 to 1.0 h, injecting the precursor solution into isopropanol, stirring for 1 to 3 min, and then centrifuging at 8000 to 10000 rpm / min for 1 to 3 min to separate the precipitate, then washing the precipitate with ethanol, and drying at 50 to 70° C. to obtain Cs3Bi2Br9 / ZnIn2S4; The molar ratio of ZnIn2S4 to cesium bromide and bismuth bromide is (0.015-0.75):1.5:1; the volume ratio is precursor solution: isopropanol = 1:5-10; 3) dispersing the Cs3Bi2Br9 / ZnIn2S4 obtained in step 2) into deionized water, stirring, centrifuging, and vacuum drying to obtain a Bi-doped ZnIn2S4 / BiOBr photocatalyst; Add 0.06-0.1 g of Cs3Bi2Br9 / ZnIn2S4 to every 10 mL of deionized water.

2. The method for preparing the Bi-doped ZnIn2S4 / BiOBr heterojunction photocatalyst according to claim 1, characterized in that: The stirring time in step 3) is 5 to 15 minutes.

3. The method for preparing Bi-doped ZnIn2S4 / BiOBr heterojunction photocatalyst according to claim 1, characterized in that each Add 0.0010-0.010 mmol ZnIn2S4 to 10 ml DMSO.

4. The method for preparing the Bi-doped ZnIn2S4 / BiOBr heterojunction photocatalyst according to claim 1, characterized in that: The molar ratio of Bi-doped ZnIn2S4 / BiOBr is BiOBr:ZnIn2S4=1:(0.015-0.075).

5. Use of the Bi-doped ZnIn2S4 / BiOBr heterojunction photocatalyst prepared by the method of claim 1 to degrade Rhodamine B pollutants under visible light irradiation.

6. The use according to claim 5, characterized in that: The Bi-doped ZnIn2S4 / BiOBr photocatalyst was uniformly dispersed in a rhodamine B aqueous solution and irradiated under visible light for 5 to 15 minutes. The concentration of the Rhodamine B aqueous solution is 20 mg / L; 20 mg of Bi-doped ZnIn2S4 / BiOBr photocatalyst is added to every 20 mL of the Rhodamine B aqueous solution.

Citation Information

Patent Citations

  • Cs3Bi2Br9 / TiO2 perovskite heterojunction and preparation method thereof, and application of Cs3Bi2Br9 / TiO2 perovskite heterojunction in photocatalytic toluene oxidation

    CN112295576A

  • In-situ generated perovskite heterojunction photocatalyst, preparation method and application

    CN115569659A

  • Nanoscale composite photocatalyst as well as preparation method and application thereof

    CN118594576A

  • Preparation method and application of type II heterostructure BiOBr / ZnIn2S4 photocatalyst

    CN118807794A

  • Preparation and degradation application of 3D / 0D ZnIn2S4 / CeO2 heterojunction nano photocatalyst

    CN118831614A